Developing Cognitive Assessment Objectives in Language Syllabus Design (European Journal of Behavioral Sciences, 2018)
As research begins to push syllabus developers more firmly towards a Content and Language Integrated Learning (CLIL) based approach to second language acquisition, content-focused courses and their development are a growing trend in Japanese tertiary education contexts. Actions by the Ministry of Education (MEXT) have reinforced this focus, and have created a need for syllabus designers to adapt their practices to incorporate content learning as a vehicle for driving second language acquisition. In turn, cognitive development, seen in CLIL theory as having a synergistic effect on linguistic and content mastery, is an area of interest for syllabus designers in Japan, especially as widely publicized context-specific teaching materials are still in earlier stages of dissemination.This study looks in detail at the relationship between cognitive domain taxonomic indicators and how they interact with linguistic development, in a specific Japanese tertiary syllabus. This study aims to improve the efficacy of this syllabus and its assessment in the following ways:1. By distinguishing students’ perceptions of difficulty in answering quiz questions based on Bloom’s and Anderson and Krathwohl’s taxonomies of the cognitive domain (1956, 2001), using a 12 item questionnaire;2. By comparing these perceptions of difficulty to the difficulty levels implied by the hierarchical nature of the taxonomies;3. To offer conclusions and suggestions made from the implications of one and two, in order to better develop course teaching and assessment for both language acquisition and content mastery.